2021
DOI: 10.1136/gutjnl-2020-323569
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir/velpatasvir with or without low-dose ribavirin for patients with chronic hepatitis C virus infection and severe renal impairment

Abstract: ObjectiveData regarding the real-world effectiveness and safety of sofosbuvir/velpatasvir (SOF/VEL) with or without low-dose ribavirin (RBV) in patients with chronic hepatitis C virus (HCV) infection and severe renal impairment (RI) are limited. We evaluated the performance of SOF/VEL with or without low-dose RBV in HCV-infected patients with chronic kidney disease stage 4 or 5.Design191 patients with compensated (n=181) and decompensated (n=10) liver diseases receiving SOF/VEL (400/100 mg/day) alone and SOF/V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 44 publications
4
34
0
1
Order By: Relevance
“…A total of seven studies satisfied our pre-defined selection criteria and were included in the meta-analysis. 4,[17][18][19][20][21][22] The flow diagram for the search strategy is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of seven studies satisfied our pre-defined selection criteria and were included in the meta-analysis. 4,[17][18][19][20][21][22] The flow diagram for the search strategy is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The seven studies that were finally incorporated in the meta-analysis included four single-centre studies (3 from India and 1 from Bangladesh) and three multicentric studies. 4,[17][18][19][20][21][22] One of the multicentric studies was conducted across 22 centres in Europe, North America and Australia, another was conducted in 18 haemodialysis centres of 3 Taiwanese cities, and the third study was conducted in 15 academic centres of Taiwan. 4,21,22 Five of the studies were prospective while the studies by Gaur et al and Liu et al were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…A drop in eGFR from baseline greater than 10 mL/min/1.73m 2 was noted in 16.5% (235/1427) and 15.9% (77/485) among patients with baseline stage 3 CKD who received sofosbuvir/ledipasvir with and without ribavirin, respectively [53]. Further evidence based on real life studies has been recently established [54][55][56][57][58][59]…”
Section: Sof-based Daas (Real World Studies)mentioning
confidence: 97%
“…Second, we did not include patients with CKD stage 4 or 5 because we have demonstrated that the SVR 12 rates of SOF/VEL with low-dose RBV were 95% and 100% in the EP and PP analyses. 42 Third, this retrospective study lacked standardized report forms for AEs and were therefore prone to reporting biases.…”
Section: Changes Of Child-pugh and Meld Scores Before And After Antiviral Treatmentmentioning
confidence: 99%